2012
DOI: 10.5507/bp.2012.036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the prognostic impact of nestin expression in non-small cell lung cancer

Abstract: Background. Nestin is an intermediary filament protein, expressed in progenitor cells of neural and muscle origin and in activated endothelium. The expression of this protein in tumours can be associated with degree of differentiation, biological potential and/or neoangiogenesis. Aims. The aim of this study was to examine the immunohistochemical expression of nestin in primary non-small cell lung carcinomas (NSCLC) and to determine its prognostic significance. Methods. Immunohistochemical detection of nestin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…They also reported nestin immunoreactivity in the peritumoral stroma (in 31% of cases), nerve bundles with tumor invasion and peritumoral vessels. Nestin positive neovascularisation has also been identified in non-small cell lung cancer, and correlated significantly with tumor stage [39]. In addition, nestin-positive blood vessels were found to be crucial for maintaining the structure of the glioma stem cell niche [15].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They also reported nestin immunoreactivity in the peritumoral stroma (in 31% of cases), nerve bundles with tumor invasion and peritumoral vessels. Nestin positive neovascularisation has also been identified in non-small cell lung cancer, and correlated significantly with tumor stage [39]. In addition, nestin-positive blood vessels were found to be crucial for maintaining the structure of the glioma stem cell niche [15].…”
Section: Discussionmentioning
confidence: 97%
“…Although the precise function of nestin remains to be elucidated, studies suggest that it may play a role in the control of cell proliferation, survival and differentiation [36]. Nestin is also a putative marker of CSCs [6,39], and recent studies have demonstrated that it is expressed in epithelial tumors, such as breast cancer [32], gastric cancer [6], and non-small cell lung cancer [39]. To the knowledge of the authors, the expression of nestin in LSCC has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of these malignant tumors have shown that nestin expression correlates to worse prognosis, and that nestin inhibition suppresses tumor cell migration, invasion, metastasis and stemness (20). Nestin expression has been also reported in lung cancers, with high nestin expression reportedly correlated with poor prognosis (21)(22)(23), lymphovascular invasion (21,24), and stemness (25) in surgically treated NSCLC cases. Nestin inhibition also reportedly reduces cell growth and invasion in SCLC (26).…”
Section: Introductionmentioning
confidence: 96%
“…In lung cancer, Nestin expression has been studied before, but mainly as a tumour cell marker . In addition, one single study indicated that Nestin positive vessels correlated with a higher tumour stage in NSCLC , although no survival data were presented, and the frequency of proliferating vessels was not assessed.…”
Section: Introductionmentioning
confidence: 99%